Glucomannan content stability of eddoe taro tuber based on parametric, non-parametric, and ammi analysis - Maretta, Delvi; Helianti, Is; Santosa, Edi; Diaguna, Ridwan; Purwono,; Sobir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The consumption of taro tuber as an energy source is widespread due to its composition of complex carbohydrates, including starch and non-starch polysaccharides. Glucomannan is one of the non-starch polysaccharides found in taro tuber and has been shown to be a dietary fiber with positive effects on health and beauty. The development of new varieties of taro tuber with high glucomannan content is challenging and requires significant effort in order to produce high-quality food. Therefore, this study aimed to investigate the stability of glucomannan content among 14 eddoe taro tuber genotypes using parametric, non-parametric, and AMMI methods, and to determine genotypes with high glucomannan stability. The experiments were conducted in three different agro-climatic locations using a randomized full-block design. Glucomannan content of taro tuber was analyzed from a mixture of corms and cormlets harvested 5 months after planting following the gravimetric method. The combined analysis of variance for glucomannan content showed significant effects of the environment, genotypes, and G×E interaction. Genotypes S7, S35, S15, S18, S17, S34, and S24 produced glucomannan levels higher than the overall average, but genotypes S7, S17, S18, and S34 consistently displayed higher glucomannan content than the average in each experimental site. Parametric and non-parametric measurements provided comparable results. Based on parametric stability analysis, genotype S34 showed high-rank stability (Wᵢ², σ²ᵢ, CVi value). Additionally, genotypes S34 and S18 demonstrated high stability according to bᵢ, and genotypes S17 exhibited stability according to the s²dᵢ value. Non-parametric stability analysis showed that S34 was the most stable genotypes base on Nassar Huehn, Kang-Rangksum, and Thennarasu theories. Genotypes S7 was also identified as stable, according to Kang-Rangksum. The AMMI analysis indicated that genotypes S34, S17, and S7 were high glucomannan yielders, with S34 displaying wide adaptation and S17 and S7 having specific location adaptation.